Karakteristik Peserta Didik Berkebutuhan Khusus (PDBK) Pada Mata Pelajaran Bahasa Arab di SMAIT Nurul Fikri Makassar - sudirman, Dwi Ratnasari S; Ulfiani; Muzakkir (Journal of Arabic Education and Linguistic, 2024)
The purpose of this research is to describe the condition of Students with Special Needs (PDBK) at SMAIT Nurul Fikri Makassar based on their characteristics. The type of research is descriptive qualitative. The data source of this research uses primary data (students, Arabic language subject teachers or special mentor teachers, and school principals) and secondary data such as the results of interview notes with teachers, books related to students with special needs and Arabic language books, and the results of field notes and other data that can be used as complementary data. Furthermore, the data collection methods used are observation methods, interview methods, and documentation methods. Research instruments in the form of observation guidelines and interview guidelines. Data management techniques are data collection, data transcription, data classification, data interpretation, and data description. While data analysis in this study is to review all available data from various sources, reduce data, compile it, and check data validity using source triangulation. The results of the research, regarding the condition of students with special needs at SMAIT Nurul Fikri Makassar, concluded that of the 9 PDBK students at SMAIT, two of them following the regular curriculum, three of them Omisi, thre of them subtituted, and one of them Omisi and subtituted. The implications of this research are Schools should select educators who not only have an educational background but also have experience or knowledge in the field of PDBK education, especially for GPK. In addition, it should organize PDBK education trainings for teachers who have not mastered the ability to manage or deal with PDBK. Teachers should determine a special strategy for teaching PDBK, because their ability to capture material is different from children in general.